1991
DOI: 10.1524/ract.1991.5253.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Am(III) with Humic Acids of Different Origin

Abstract: The complexation of Am(III) with two humic acids from different origins has been investigated in 0.1 Μ NaC10 4 at pH = 6.0 by UV spectroscopy and radiometric measurement. Both humic acids, extracted from Gorleben groundwater and purchased from Aldrich Co., are purified, protonated and characterized previously. Loading capacities of two humic acids for the Am 3 + ion are determined and taken into account for the evaluation of complexation constants. Experiment verifies a tridentate complexation of Am(III) for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 10 publications
5
43
2
Order By: Relevance
“…Combining Equations (5)- (10), the fraction of the ligand bound can be expressed as Equation (11). (5)- (10), and approximating the term [NO 3 …”
Section: Eu(iii)-binding Abilities Of Horonobe Groundwater Hssmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining Equations (5)- (10), the fraction of the ligand bound can be expressed as Equation (11). (5)- (10), and approximating the term [NO 3 …”
Section: Eu(iii)-binding Abilities Of Horonobe Groundwater Hssmentioning
confidence: 99%
“…Since the extent of binding of radionuclides to deep groundwater HSs is a factor in the degree of the effect, an understanding of this process is an essential subject. In previous studies, the binding abilities of radionuclides have been extensively investigated for HSs isolated from deep groundwaters in a sedimentary rock layer in Gorleben, Germany, and in granitic rock layers in Fja¨llveden, Sweden, and Fanay-Auge`res, France [3][4][5]. These studies indicated that deep groundwater HSs had same degree of affinities for binding radionuclides as HSs obtained from Aldrich and from surface environments.…”
Section: Introductionmentioning
confidence: 97%
“…PbOH + or PbCl + and to adsorption on or co-precipitation with colloidal particles in groundwaters [213], Strong hydrolysis of thorium and polonium, and the extremely low solubility of their oxides/hydroxides are the reason why 232 Th, 230 Th and 2W Po migrate in groundwaters mainly in colloidal forms [214][215][216], Underground repositories of radioactive wastes and the transport of radionuclides from contaminated soils or surface waters may represent significant sources of artificial radionuclides in groundwaters. Release and migration of radionuclides from nuclear wastes strongly depend on their chemical composition and on the speciation of the released radionuclides.…”
Section: Groundwatersmentioning
confidence: 99%
“…Colloids may be released from nuclear wastes, or may be formed by precipitation of sparingly soluble compounds of radionuclides and by association of radionuclides with inorganic or organic colloids ('Fremdkolloide', [226,227]) present in groundwaters [214,[228][229][230] [231] were able to show that U(VI), Am(III), Cm(III), and Th were strongly sorbed to aquatic colloids, rich in humic and fulvic substances, whereas Np(V) was negligibly sorbed to these colloids.…”
Section: Groundwatersmentioning
confidence: 99%
See 1 more Smart Citation